Hubungan Ibu Hamil Trimester III Dengan Tingkat Kecemasan Dalam Menghadapi Persalinan Di UPTD Puskesmas Trimoharjo - Pratiwi, Widya Sandy; Yuliaswati, Enny; Widiyati, Rina Sri; Handayani, Sri (CV. Ulil Albab Corp, 2024)
Pregnant women will certainly have significant changes and impacts related to physiological and psychological. The occurrence of physiological changes such as nausea, vomiting, an enlarged stomach, and fatigue can certainly affect the mother's psychology during pregnancy. However, due to physiological and psychological changes that occur during pregnancy, this then triggers feelings of anxiety (anxiety) and feelings of anxiety in the condition of pregnancy. This type of research is analytic using the research design